2023
DOI: 10.3390/app13042249
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Graffiti Detection: A Study Using Images from the Streets of Lisbon

Abstract: This research work comes from a real problem from Lisbon City Council that was interested in developing a system that automatically detects in real-time illegal graffiti present throughout the city of Lisbon by using cars equipped with cameras. This system would allow a more efficient and faster identification and clean-up of the illegal graffiti constantly being produced, with a georeferenced position. We contribute also a city graffiti database to share among the scientific community. Images were provided an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Killen et al conducted a comprehensive analysis of six studies on the social background and motivation behind railroad-related graffiti vandalism, as well as the technological and non-technological mitigation measures employed. In one of the studies, the authors presented a deep-learning-based methodology for robust graffiti detection, as reported in [4]. While CCTV surveillance and geographical information systems (GISs) are employed to record and identify geographical patterns in vandalism activities, it is also observed that the presence of surveillance can have unintended consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Killen et al conducted a comprehensive analysis of six studies on the social background and motivation behind railroad-related graffiti vandalism, as well as the technological and non-technological mitigation measures employed. In one of the studies, the authors presented a deep-learning-based methodology for robust graffiti detection, as reported in [4]. While CCTV surveillance and geographical information systems (GISs) are employed to record and identify geographical patterns in vandalism activities, it is also observed that the presence of surveillance can have unintended consequences.…”
Section: Introductionmentioning
confidence: 99%